2007
DOI: 10.1111/j.1467-7660.2007.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Driven Development, Collective Action and Elite Capture in Indonesia

Abstract: In response to the well documented limitations of top‐down, modernist and authoritarian approaches that have dominated development, practitioners and academics increasingly promote more community‐based approaches. The World Bank uses the term ‘community driven development’ to describe projects that increase a community's control over the development process. In an analysis of a community driven poverty alleviation project in Indonesia, this article examines the vulnerability of such an approach to elite captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
219
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(247 citation statements)
references
References 68 publications
7
219
0
3
Order By: Relevance
“…Elite capture is clearly a problem for some FFS programmes and may stem from the fact that FFS training can largely be regarded as a private and not a public good. Dasgupta and Beard (2007) and Alatas et al (2013) have shown that community-based targeting does not necessarily lead to elite capture and that it can be effective in identifying the most deserving community members, a finding supported by this analysis.…”
Section: Resultssupporting
confidence: 70%
“…Elite capture is clearly a problem for some FFS programmes and may stem from the fact that FFS training can largely be regarded as a private and not a public good. Dasgupta and Beard (2007) and Alatas et al (2013) have shown that community-based targeting does not necessarily lead to elite capture and that it can be effective in identifying the most deserving community members, a finding supported by this analysis.…”
Section: Resultssupporting
confidence: 70%
“…Anthropologists warned about elite capture in community-driven projects that prevent them from benefiting the truly poor (e.g. Dasgupta and Beard 2007). One can infer from this that RI, if it does not start paying attention to unequal power relations and situations in which irreconcilable diverging interests come up, risks becoming similarly hollow.…”
Section: Family Resemblances: Insights From Related Research Fieldsmentioning
confidence: 99%
“…Source: Pretty (1995) As empowerment places people as main actors, the success of empowerment is highly dependent on the response, involvement, and responsibility of the community towards community empowerment programs, or in other words at the level of community participation. Community empowerment requires the following conditions in order to create a participatory role throughout the whole local community (Dasgupta, 2007): (a) decentralization, (b) democracy, and (c) collective action. The level of success of any community-driven development program using a participatory approach will be high in communities that have a high level of participation, have equality among its members, and have high competence for dialogue (Sufianti, 2014).…”
Section: Criteriamentioning
confidence: 99%